La enseñanza del movimiento parabólico a través del software Tracker en estudiantes del nivel de bachillerato - Martínez Sarango, Jostin Jasmany (2025)
The teaching of parabolic motion presents challenges due to the large number of physical quantities involved and the relationship between them. Therefore, the objective of this research was to determine the processes that improve the teaching of parabolic motion in high school students. It began with a systematic documentary review process in Scopus, Dialnet, Scielo, Redalyc, in the search engine, Google, and for the process of selection and organization of the information it was carried out with the support of search logs, bibliographic and content files. Based on the theoretical results, a field phase was used, starting with the planning of six seminars-workshops framed in parabolic movement mediated with Tracker software, aimed at high school students of a public educational institution in the city of Loja. These were executed in six class sessions of 80 minutes each. Finally, a questionnaire was applied to the students to measure the level of satisfaction with the implemented methodology. As a systematic documentary result, it was obtained that the most common methodological process for teaching Physics consists of three cyclical phases: beginning, development and closing. In development phase, it is included digital tools such as tracker. From the classroom experience with Tracker, it was obtained a high level of satisfaction of the students and a good qualification in one closing workshop, showing a significant correlation of 0.783 between these magnitudes, so it is concluded that, to execute seminars-workshops mediated with Tracker to teach parabolic motion, becomes a recommended didactic process.